Rabbit Pellet Formula Study using Animal Feed Calculator - ghazali, khadijah; Baseri , Najihah; abdul rahman, misbahul muneer (Multidisciplinary Applied Research and Innovation, 2023)
Current rabbit farmers are too dependent on commercial rabbit pellet and this led to high rabbit meat price. This study, first objective is to study suitable ingredients for rabbit pellet based on their nutrients content. Second objective is to produce rabbit feed formula using animal feed calculator. The third objective is to produce rabbit feed formula which is 20%-30% cheaper than commercial price (RM 27 per 3 kg). The Hand Pearson Square Method was used to identify rabbit pellet formula. To speed up the calculation process, the Hand Pearson Square Method was converted into Microsoft Excel and rabbit feed formula was expected to cost approximately RM 27 per 3 kg to produce. All the ingredients must be weighed according to the animal calculator feed formula for gestation rabbit. Water spinach, pineapple, carrot, cucumber, molasses, soybean hull, sunflower seed, anchovies head which are 140 g, 140 g, 10 g, 70 g, 150 g, 500g, 40 g, and 270 g. All ingredients mix well with molasses and add water little by little until get the dough texture then it can be shaped using meat mincer. For drying process, the pellet is dry in the oven at 50 to 60 Celsius until the pallet is dried completely. Result shows the value of rabbit pallet for gestation stages using animal feed calculator for crude protein which is 21.22%, crude fibre is 16.83%, calcium is 1.63%and phosphorus is 0.41% meet the requirement in Department of Veterinary Services. In Department of Veterinary Services, the nutrition content (%) for crude protein is 21.3%, crude fibre is 16.8%, calcium is 0.03% and phosphorus is 0.59% for gestation stage. Cost to produce rabbit pallet is approximately for 3 kg pallet is RM 25.35. Good palatability pallet is when the mixture ingredients mixed with wheat powder to get pallet shaped.